Martin Kagel and David Z. Saltz, editors. Open Wounds. Holocaust Theater and the Legacy of George Tabori. University of Michigan Press, 2022. - Janine Wulz (Studies in 20th & 21st Century Literature, 2024)
Review of Martin Kagel and David Z. Saltz, editors. Open Wounds. Holocaust Theater and the Legacy of George Tabori. University of Michigan Press, 2022.
Keywords: review; Holocaust; theater